2018
DOI: 10.1021/acs.jpclett.8b02811
|View full text |Cite
|
Sign up to set email alerts
|

How Lattice Dynamics Moderate the Electronic Properties of Metal-Halide Perovskites

Abstract: Metal-halide perovskites have emerged as highly promising semiconductors with excellent optoelectronic properties. This Perspective outlines how the dynamic response of the ionic lattice affects key electronic properties such as exciton binding energies and charge-carrier mobilities in hybrid perovskites. Such links are shown to derive from the frequency-dependence of the dielectric function, which is governed by contributions from electronic interband transitions, polar vibrations of the metal-halide sublatti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
204
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(224 citation statements)
references
References 103 publications
8
204
0
Order By: Relevance
“…In a previous work, we determined the exciton-exciton annihilation rate to be 0.41 cm 2 s −1 for monolayer WS 2 46 , similar to other TMDCs 47 , which is more than one order of magnitude higher than that of n = 1. This large difference in exciton annihilation rates given similar exciton binding energies in two materials is intriguing and could be related to the unique dielectric function of hybrid perovskites, for instance, as the result of the motion of the polar organic cations 48 . Further, an advantage brought by the highly tunable structure of 2D perovskites is the ability to modulate Coulomb interactions to suppress annihilation through composition tuning.…”
Section: Resultsmentioning
confidence: 98%
“…In a previous work, we determined the exciton-exciton annihilation rate to be 0.41 cm 2 s −1 for monolayer WS 2 46 , similar to other TMDCs 47 , which is more than one order of magnitude higher than that of n = 1. This large difference in exciton annihilation rates given similar exciton binding energies in two materials is intriguing and could be related to the unique dielectric function of hybrid perovskites, for instance, as the result of the motion of the polar organic cations 48 . Further, an advantage brought by the highly tunable structure of 2D perovskites is the ability to modulate Coulomb interactions to suppress annihilation through composition tuning.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, for clarity and consistency we present values in terms of the apparent bimolecular recombination rate constants φk 2 and effective charge‐carrier mobilities φμ (see Section H in the Supporting Information). For 3D lead halide perovskites φ = 1 can be assumed, given that excitonic effects at room temperature are negligible as a result of the low exciton binding energy . For Ruddlesden‐Popper systems with low n‐values, greater electronic confinement effects and larger exciton binding energiesare present, meaning that φ could potentially be smaller than one.…”
Section: Resultsmentioning
confidence: 99%
“…[48,49] While optical phonons, leading to the formation of large polarons would predict the experimentally found mobilities much better, the temperature dependence of the mobility is described more accurately by acoustic phonons. [50] That is, acoustic phonons predict that μ ∝ T −1.5 , whereas for polarons this is T -0.5 . [48,51,52] Since we and others have found that for many [47] Interestingly, not only the mobility but also the lifetime of mobile charges follow the same temperature dependence in MAPbI3 and CsPbI3, as shown in Figure 7b.…”
Section: Section 4: Temperature Dependence Of Charge Carrier Dynamicsmentioning
confidence: 99%